Inherited DNA amplification of the proximal 15q region: cytogenetic and molecular studies. Issue 3 (March 1997) - Mignon, C; Parente, F; Stavropoulou, C; Collignon, P; Moncla, A; Turc-Carel, C; Mattei, M G
Abstract : In a 15 year old girl, referred for growth retardation, conventional cytogenetic analysis detected an abnormal 15q+ chromosome with extra material in the proximal region, inherited from her father and grandfather. Using various molecular cytogenetic techniques, including comparative genomic hybridisation, we showed that the extra chromatin resulted from in situ amplification of DNA sequences located between the loci D15Z1 and D15S18. On the basis of the clinical features of our patient and the late replication of the large amplified region, we searched for functional modifications in the adjacent Prader-Willi syndrome region.